Toward Freedom and Dignity The Humanities and the Idea of Humanity - Hardison, Jr (Johns Hopkins University Press, 2019)
Originally published in 1973. Toward Freedom and Dignity is a humanist's view of the humanities in an age of burgeoning technology. O. B. Hardison Jr. deals with the status of the humanities and their future-how they are regarded and how they may come to contribute to a genuinely humane society. He argues that humanistic studies are not a luxury in either education or society. They are central to the preparation of human beings for the kind of society that is possible if we manage to avoid an Orwellian technocracy. Social goals and priorities must be set in terms of the ideal of a culture truly adjusted to human needs and human limitations. In framing his argument, Hardison draws on ideas of the humanities since the Renaissance, especially on the philosophical humanities that emerged in Europe in the works of authors like Kant, Schiller, and Coleridge. He is untroubled by anti-humanistic trends in college curricula and the surrounding culture, and he contends that we have only one practical option: to ensure that culture evolves toward a more humane society, toward freedom and dignity.